Sequencing and analysis of the complete mitochondrial genome of Hippopus porcellanus. Issue 9 (2nd September 2021) - Ma, Haitao; Zhang, Baolu; Zhang, Yuehuan; Zhang, Yang; Qin, Yanping; Han, Chenghui; Chen, Shixi; Yu, Ziniu
Abstract: In this study, the complete mitochondrial genome of Hippopus porcellanus was reported. The whole mitochondrial genome was 21, 565bp in length with a typical mitochondrial genomic structure including 13 protein-coding genes, 23 transfer RNA genes, 2 ribosomal RNA genes and 1 control region (D-loop). Mitogenome base composition was biased toward A + T content, at 60.3%. A phylogenetic tree based on complete mitogenome sequences revealed that, H. porcellanus is closely related to H. hippopus, both of which belong to the genus Hippopus .